L’enseignant et le jeu : de l’expérience de joueur à l’enseignement du jeu ? - Vanessa Desvages-Vasselin; Pablo Buznic-Bourgeacq (Recherches en Éducation)
As playing is not common practice in primary schools, we question the place of games and their authenticity during teaching periods and more specifically the teacher’s reasons for letting children play or not. This article is based on a research about the uses of games in primary schools. To start with, we have questioned the rightfulness of games at school in order to identify the tensions wich are inherent to these practices. Our analysis has focused on the teacher himself, as he appears to be the last and deepest motivation of these tensions, and on his subjective position about games in the classroom. With this aim, we have analyzed the play pratices of three primary school teachers confronted with the integration of games in their teaching methods.